Modelling of Thin Films Hardness Measured by a Spherical Indenter - Boudilmi, A.; Loucif, K. (Металлофизика и новейшие технологии, 2018)
In this theoretical contribution, we chose to use an indenter having a spherical geometrical form, which we used to model the surfaces mixture to separate the contributions of substrate and film in the composite covered material hardness. We have considered the coefficients α, β of the model as ratios of the projections of the imprints at the horizontal plans (disks surfaces). We prove that the film hardness of monolayer coating is dependent on the composite and substrate hardness, the geometrical form of the indenter, and the film thickness. В этой теоретической работе рассмотрен индентор сферической геометрической формы, который был использован для составления модели смешанных поверхностей, чтобы оценить вклады подложки и плёнки в твёрдость композитного материала покрытия. Коэффициенты модели α, β рассматриваются как отношения проекций отпечатков на горизонтальные плоскости (в виде дисков). Доказано, что твёрдость плёнки однослойного покрытия зависит от твёрдостей композитного покрытия и подложки, геометрической формы индентора и толщины плёнки. У цій теоретичній роботі розглянуто індентор сферичної геометричної форми, який було використано для складання моделю змішаних поверхонь, щоб оцінити внески підкладинки та плівки у твердість композитного матеріялу покриття. Коефіцієнти моделю α, β розглядаються як співвідношення проєкцій відбитків на горизонтальні площини (у вигляді дисків). Доведено, що твердість плівки одношарового покриття залежить від твердостей композитного покриття та підкладинки, геометричної форми індентора та товщини плівки.